Ageing Mediterranean Bluefin Tuna: A Comparative Study Between Dorsal Fin Spines and Vertebrae - Niki Milatou; Persefoni Megalofonou (Fishes, 2025)
This study estimated the age and growth of reared Atlantic bluefin tuna by analyzing two calcified structures: the caudal vertebrae and the dorsal fin spines. The aim was to compare the two ageing methods. A total of 613 dorsal fin spines and 613 vertebrae were aged, with each pair of calcified structures derived from the same individual fish. The age of each fish was determined from the number of visible growth bands on the structures. The estimated ages ranged from 4 to 20 years for dorsal fin spines and from 5 to 17 years for caudal vertebrae. Both calcified structures were demonstrated to be suitable for ageing bluefin tuna. The percent agreement between the two methods was high in medium-sized fish but lower in larger fish. Additionally, the results showed a tendency to estimate fewer years in vertebrae than in dorsal fin spines for fish older than 11 years. For the samples where no bias was found between the two ageing methods (N = 215), the von Bertalanffy growth model was fitted to the mean lengths at estimated ages, with the growth parameters determined as follows: L∞ = 372.3 cm, k = 0.075 yr−1, and t0 = −1.292 yr. This research makes a novel contribution to the field by conducting a direct, large-scale comparison of age estimates derived from two different calcified structures, addressing a notable gap in the literature and offering critical insights into the consistency and reliability of ageing methods used in stock assessment.